Dual-Converter Active Power Filter with Reduced Dynamic Losses: Control Synthesis and Modelin - A. V. Belousov; Y. V. Skuriatin; N. A. Denysevich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Nowadays, active power filters represent one of the most efficient means to reduce inactive power components which provides proper quality of electricity at common network connectivity points. Dynamic power losses in the valves that have a significant impact on the efficiency of the converter and, accordingly, determine the feasibility of using these filters in each specific situation, are among their key parameters. Along with the solution of the problem of ensuring the proper quality of electricity at common network connectivity points, the task of reducing dynamic losses in the valves becomes especially relevant. The purpose of the study is to increase the efficiency of active filtration in terms of reducing dynamic losses in the valves while ensuring high-quality voltages at common network connectivity points and currents consumed from the network. To achieve the goal, it is proposed to jointly use a dual-converter active power filter operating in a mode with different conversion frequencies and rated converter capacities, and an interface LCL-filter. Synthesis of converter control is performed. As a control method, the sliding mode control has been used. The efficiency of the proposed system was assessed by modeling in the MATLAB-Simulink application software package. The simulation results confirm the possibility of organizing a mode of operation in which the conversion frequencies and rated capacities of the converters of active power filters are different. In such a case, the currents and voltages consumed from the network at common network connectivity points have an almost perfect harmonic shape; and the phase shift of the network currents relative to the corresponding voltages has a negligible value. It is shown that the organization of the operating mode of converters with different conversion frequencies and rated capacities can significantly reduce the dynamic losses in the switches of active power filters.